Plan de marketing para el fortalecimiento de las ventas de la empresa textil Confecciones CECY - Ayala, Joselin C. (2019)
The present project is directed to the textile company Confecciones Cecy, created on May 14, 2000, the main objective of the company is to strengthen sales that has decreased in the last four months of the year 2018. The work basically consists in the design of an international marketing plan for the garments that the company manufactures. The garments that the company commercializes the most are girls' blouses made of cotton and knit, which are elaborated with a rigorous process of quality, where the best raw material and the participation of qualified employees are used. The garments mentioned above have a great reception in the local market, it is because the company has exclusive designs for every taste and preference of the client.This investigation consists of three chapters which are structured as follows: theoretical framework; makes reference to the theoretical concepts based on bibliographic data. Methodological development; It details the techniques and tools to be used for the development of the international marketing plan. Analysis of results; indicates the development of the marketing plan. It is concluded that the design of an international marketing plan is of help and improvement for the growth of the company itself and helps the employment of more people and improves the economy of it.